2013
DOI: 10.1103/physrevd.88.015001
|View full text |Cite
|
Sign up to set email alerts
|

Composite millicharged dark matter

Abstract: We study a composite millicharged dark matter model. The dark matter is in the form of pionlike objects emerging from a higher scale QCD-like theory. We present two distinct possibilities with interesting phenomenological consequences based on the choice of the parameters. In the first one, the dark matter is produced non-thermally and it could potentially account for the 130 GeV Fermi photon line via decays of the "dark pions". We estimate the self-interaction cross section which might play an important role … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 88 publications
(132 reference statements)
0
14
0
Order By: Relevance
“…It is also possible that hidden sector contains millicharged fields, and this possibility also results in viable DM candidates[344] 7. Another possibility is to introduce a new electromagnetically charged scalar, so that the freeze-in production of sterile neutrinos occurs via decay of the charged scalar to a sterile neutrino and a charged SM lepton[346].…”
mentioning
confidence: 99%
“…It is also possible that hidden sector contains millicharged fields, and this possibility also results in viable DM candidates[344] 7. Another possibility is to introduce a new electromagnetically charged scalar, so that the freeze-in production of sterile neutrinos occurs via decay of the charged scalar to a sterile neutrino and a charged SM lepton[346].…”
mentioning
confidence: 99%
“…(4) However as we shall argue, if dark matter (DM) is in the form of millicharged particles (MC) (as for example [8], [9]), accretion of DM onto the NS can lead to an excess of electric charge that due to overall electric neutrality must be expelled from the caps, providing this way an extra component of current. On generic grounds, let us assume that the total current has two components, I = I GJ + I DM , where I DM represents the extra current due to external accretion from the MCDM galactic distribution where the NS may be located [10].…”
mentioning
confidence: 99%
“…In fact, we found that dispersion due to matter effects was irrelevant until energies around 10 29 GeV. But composite DM models might prove to be more reactive, particularly if the DM is comprised of charged constituents [29,30,35,37,42,44,45,47,48,50,52,53,58,59].…”
Section: Introductionmentioning
confidence: 88%